2020
DOI: 10.7196/samj.2020.v110i11.15222
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lockdown regulations on SARS-CoV-2 infectivity in Gauteng Province, South Africa

Abstract: The rapid spread of COVID-19 has resulted in a global pandemic. [1] By 10 July 2020, 22 million cases had been reported worldwide, resulting in 580 000 deaths. Governments around the world have implemented variable lockdown regulations to curb the rapid transmission of SAR-CoV-2. The first South African (SA) case of COVID-19 was reported on 5 March. [2] On 26 March, the SA government initiated a 21-day national level 5 lockdown. [3] The strict regulations included restriction of population mobility and interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The effectiveness of measures such as universal lockdowns and closures of businesses and schools for the containment of covid-19 have largely been effective, but depended on early implementation when incidence rates of covid-19 were still low 425258. Only Japan reported no decrease in covid-19 incidence after school closures,44 and other studies found that different public health measures were sometimes implemented simultaneously or soon after one another, thus the results should be interpreted with caution 324656…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of measures such as universal lockdowns and closures of businesses and schools for the containment of covid-19 have largely been effective, but depended on early implementation when incidence rates of covid-19 were still low 425258. Only Japan reported no decrease in covid-19 incidence after school closures,44 and other studies found that different public health measures were sometimes implemented simultaneously or soon after one another, thus the results should be interpreted with caution 324656…”
Section: Discussionmentioning
confidence: 99%
“…Pillai et al concluded that the number of Covid-19 positive patients increased with the easing of lockdown regulations to level 3 in Gauteng, which is consistent with our data. 31 In the Covid-19 positive population, demographics, fracture pattern and mechanism of injury were similar to that of Covid-19 negative patients.…”
Section: Discussionmentioning
confidence: 78%
“…Since the early days of the SARS-CoV-2 pandemic in 2020, inequalities in case, hospitalisation and death rates have been noted internationally 1–8. The most deprived populations and areas in the USA, Europe and other high-income countries (in terms of a range of deprivation measures) have suffered up to twice the mortality rates of the least deprived sections of society 2 7 9–12.…”
Section: Introductionmentioning
confidence: 99%